Legal Protection for Prospective Notaries Against Unfinished Notary Obligations When the Notary Dies - Munnofa, Artha; Istislam; Hadisuryo, Hendrarto (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The death of a notary before completing his or her duties can cause legal problems, especially since unsigned deeds are not included in the notary protocol as per the Explanation of Article 62 of UUJN-P. This threatens the rights of prospective notaries, including down payments and important documents that have been submitted. UUJN-P does not regulate the duties of a notary who dies while performing his/her duties or who is responsible for completing those duties. While Article 1 point 2 and Article 35 paragraph (3) of UUJN-P explain that temporary notary officials are in charge of replacing notaries who die while on leave, there is no provision for notaries who die while on duty. Article 35 paragraph (1) of UUJN-P only requires the notary's heirs to report the death to the MPD, without the obligation to continue the unfinished deed. This creates a norm void that has the potential to harm prospective notaries. Therefore, legal protection for prospective confrontants is needed to overcome this norm vacuum and prevent material losses. In order to analyze the problems in this study, a normative juridical research method is used, namely research by examining formal regulations such as legislation, literature that is theoretical in nature to then be related to the problems discussed. in examining legal issues related to legal protection for the faces of the unfinished duties of the Notary's office when the notary dies is based on the existence of legal uncertainty in the laws and regulations related to the notary's office, that there is a norm vacuum against the completion of the unfinished duties of the Notary's office when the notary dies. The results of the research in brief are that legal protection for prospective notaries when the notary dies before completing his duties is important to protect their rights. Internal protection in the form of a written agreement between the notary and the prospective confrontant before the deed is made serves as proof of document deposit and down payment.